2022
DOI: 10.1111/jam.15620
|View full text |Cite
|
Sign up to set email alerts
|

L-norvaline affects the proliferation of breast cancer cells based on the microbiome and metabolome analysis

Abstract: Aims:The altered faecal metabolites and microbiota might be involved in the development of breast cancer. We aimed to investigate the effect of differential metabolites on the proliferative activity of breast cancer cells. Methods and Results:We collected faecal samples from 14 breast cancer patients and 14 healthy subjects. Untargeted metabolomics analysis, short-chain fatty acid (SCFA) targeted analysis, and 16S rDNA sequencing was performed. The gut metabolite composition of patients changed significantly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…( 61 ) gave opposite results as the study by Zhu et al. ( 60 ) in case of isobutyrate. The differences in the results may be caused by the type of samples used in the studies, i.e.…”
Section: Scfas In Oncological Diseasesmentioning
confidence: 65%
See 1 more Smart Citation
“…( 61 ) gave opposite results as the study by Zhu et al. ( 60 ) in case of isobutyrate. The differences in the results may be caused by the type of samples used in the studies, i.e.…”
Section: Scfas In Oncological Diseasesmentioning
confidence: 65%
“…Zhu et al. ( 60 ), performed untargeted metabolomics, targeted metabolomics (SCFAs), and 16 S rDNA sequencing studies on fecal samples from 14 breast cancer patients and 14 healthy volunteers. The SCFAs content in fecal samples was analyzed quantitatively.…”
Section: Scfas In Oncological Diseasesmentioning
confidence: 99%
“…The LEfSe and the genus level heatmap analysis revealed higher abundance of Rothia genus in tumor tissues. A previous study showed that Rothia abundance in fecal samples of breast patients was negatively correlated with the level of the gut amino acid metabolite norvaline [ 35 ]. In the same study, they used L-norvaline, a type of norvaline, to investigate the inhibitory effect of L-norvaline on BC 4 T1 cells, as well as the relation between the L-norvaline concentration and the arginase1 level (Arg-1).…”
Section: Discussionmentioning
confidence: 99%
“…However, yric acid plays multiple roles in breast cancer cells, including inhibitors of histone deacetylases (epigenetic modulators), metabolic substrates, and ligands of free fatty acid receptors (reviewed in [44]. However, yric acid levels decrease in the feces of breast cancer patients [41].…”
Section: Discussionmentioning
confidence: 99%